Un paso adelante y dos atrás: Movimiento indígena, democracia y política en Ecuador - Rivera Vélez, Fredy (2006)
In the last two decades, Ecuador has been exposed to a series of economic and political problems that have affected democratic governance, the full observance of human rights and the possibility of building effective, legitimate and representative institutions, under a framework conducive to the social and economic development of its inhabitants. In broad terms, these problems have cast doubt on the immediate future regarding the constitution of an effective rule of law that expresses respect for the rules of the democratic game, by the different actors of civil society and government authorities.